Gout in history of humanity - M. S. Eliseev; Ya. I. Kuzmina; E. L. Nasonov (Научно-практическая ревматология, 2024)
Gout has the richest history of all rheumatic diseases. The name of this most ancient of the described diseases of the musculoskeletal system for a long time not only determined the fact of damage to the joints, but was also synonymous with severe pain. Although the disease itself is much older than humanity and dates back to prehistoric times, it was with the advent of man on Earth that gout began to influence the historical process and became an integral part of it. Since ancient times, it was noticed that famous kings, emperors, generals, admirals and philosophers, musicians and artists, scientists and writers often suffered from gout. The cause of the disease was seen in a sedentary lifestyle, overeating, and abuse of wine with significant mental stress. And now it is difficult to imagine our world without this disease, which is so closely intertwined with the history of humanity.